Congestive heart failure in three dogs - Mahmut Ok; Aliye Sağkan Öztürk; Cenk Er (Eurasian Journal of Veterinary Sciences)
In this case report the clinical, hematological, blood gases, some biochemical, ultrasonographic, electrocardiographic (ECG), radiographic and necropsy findings were presented in three dog with congestive heart failure. Plasma cardiac troponin I (cTnI) and creatinin kinase isoenzyme MB (CKMB) concentrations of all dogs were significantly increased. In the electrocardiagraphic examination, one dog had atrial fibrillation and two dogs had ventricular tachycardia. Radiographic and ultrasonograhpic examination, left and right heart dilatation was observed in all cases.